Intentions vs. Implementation of Philippine Economic Reforms Under Aquino Government, 1986-1992 - V. Bruce J. Tolentino (Philippine Institute for Development Studies (PIDS), 1994)
This paper explains the gaps between official objectives and the actual accomplishments of the Aquino government, with an emphasis on the implementation record of agricultural-based strategies. Summary of the lessons learned is provided.
Keywords: 330; agriculture sector; economic reform; investment; poverty; employment opportunities; savings; crop production; current account